THE USE OF PLANTS TO PROTECT PLANTS AND FOOD AGAINST FUNGAL PATHOGENS: A REVIEW - Shuping, D.S.S.; Eloff, J.N. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Plant fungal pathogens play a crucial role in the profitability, quality and quantity of plant production. These phytopathogens are persistent in avoiding plant defences causing diseases and quality losses around the world that amount to billions of US dollars annually. To control the scourge of plant fungal diseases, farmers have used fungicides to manage the damage of plant pathogenic fungi. Drawbacks such as development of resistance and environmental toxicity associated with these chemicals have motivated researchers and cultivators to investigate other possibilities. Materials and Methods: Several databases were accessed to determine work done on protecting plants against plant fungal pathogens with plant extracts using search terms “plant fungal pathogen”, “plant extracts” and “phytopathogens”. Proposals are made on the best extractants and bioassay techniques to be used. Results: In addition to chemical fungicides, biological agents have been used to deal with plant fungal diseases. There are many examples where plant extracts or plant derived compounds have been used as commercial deterrents of fungi on a large scale in agricultural and horticultural setups. One advantage of this approach is that plant extracts usually contain more than one antifungal compound. Consequently the development of resistance of pathogens may be lower if the different compounds affect a different metabolic process. Plants cultivated using plants extracts may also be marketed as organically produced. Many papers have been published on effective antimicrobial compounds present in plant extracts focusing on applications in human health. More research is required to develop suitable, sustainable, effective, cheaper botanical products that can be used to help overcome the scourge of plant fungal diseases. Conclusions: Scientists who have worked only on using plants to control human and animal fungal pathogens should consider the advantages of focusing on plant fungal pathogens. This approach could not only potentially increase food security for rural farmers, lead to commercial rewards, but it is also much easier to test the efficacy in greenhouse or field experiments. Even if extracts are toxic it may still be useful in the floriculture industry.